2016
DOI: 10.1161/hypertensionaha.115.06345
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic Genome-Wide Meta-Analysis of Blood Pressure Response to β-Blockers in Hypertensive African Americans

Abstract: African Americans suffer a higher prevalence of hypertension compared to other racial/ethnic groups. In this study, we performed a pharmacogenomics genome-wide association study of blood pressure response to β-blockers in African Americans with uncomplicated hypertension. Genome-wide meta-analysis was performed in 318 African American hypertensive participants in the two Pharmacogenomic Evaluation of Antihypertensive Responses studies: 150 treated with atenolol monotherapy and 168 treated with metoprolol monot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 25 publications
(28 reference statements)
0
52
0
Order By: Relevance
“…Growing evidence indicates that adrenergic receptor density, distribution and function, and consequent vasomotor activity are determined in part by genetics, accounting for some of the individual differences both between and within racial groups [34,35]. A recent pharmacogenomics genome-wide meta-analysis of BP responses to β-blockers in African-Americans showed that two genotype variants were related to the antihypertensive efficacy of atenolol and metoprolol [36]. A study examining the effects of β 1 -adrenergic receptor polymorphisms on the response to β-blockade, however, found that racial differences could not be fully explained by different distributions of functional β 1 -adrenergic receptor variants [37].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence indicates that adrenergic receptor density, distribution and function, and consequent vasomotor activity are determined in part by genetics, accounting for some of the individual differences both between and within racial groups [34,35]. A recent pharmacogenomics genome-wide meta-analysis of BP responses to β-blockers in African-Americans showed that two genotype variants were related to the antihypertensive efficacy of atenolol and metoprolol [36]. A study examining the effects of β 1 -adrenergic receptor polymorphisms on the response to β-blockade, however, found that racial differences could not be fully explained by different distributions of functional β 1 -adrenergic receptor variants [37].…”
Section: Discussionmentioning
confidence: 99%
“…A GWAS of atenolol and metoprolol BP response was conducted in a cohort of AfricanAmerican, hypertensive participants from the PEAR studies 85 . Two replicated variants, rs201279313 in SLC25A31 and rs11313667 in LRRC15, were found to predict improved BP response to β-blocker monotherapy in African Americans.…”
Section: Plausible Variants Uncovered In Unbiased Analysesmentioning
confidence: 99%
“…changes in diet, exercise, time-of-day, combinations of prescribed drugs, alcohol usage, etc .). Several PGx GWAS have reported variants in plausible genes associated with thiazide diuretics (Chittani et al, 2015; Turner et al, 2008; Turner et al, 2013), angiotensin II receptor blockers (Frau et al, 2014; Turner et al, 2012), and beta-blockers (Gong et al, 2015; Gong et al, 2016); yet, most of these studies involve relatively small discovery sample-sizes and are underpowered, as far as detecting associations having genome-wide significance ( i.e. P < 5 × 10 −8 ).…”
Section: Genetic Studies Of Pgx Traitsmentioning
confidence: 99%